Experimental validation of a tactile sensor model for a robotic hand - Yahud, S.; Dokos, S.; Morley, J.W.; Lovell, N.H. (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/